Peran Media Sosial, Biaya UKT, dan Citra Merek Mempengaruhi Keputusan Melanjutkan Studi di Universitas Budi Luhur : (Studi pada Mahasiswa Universitas Budi Luhur Angkatan 2024) - Marsudin Putra Jaya Gulo; Yugi Setyarko (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research aims to determine the role of social media, single tuition fees (UKT), and brand image on the decision to continue studying at Budi Luhur University, South Jakarta. In this study the population is known. The sample used in this research was 100 respondents, using a simple random sampling method and using the Slovin formula. In this research, the data was analyzed using the SPSS 26 program with Microsoft Excel 2016. The results showed that Social Media had a significant influence on the Decision to Continue Studying, UKT Fees did not have a significant influence on the Decision to Continue Studying, and Brand Image had a significant influence on the Decision to Continue Studying.